Leadership Practices and Research Capability Development: A Qualitative Study of Faculty Experiences in Internationalizing Higher Education Institutions - Labrador, Jihan A. (Archives of Business Research, 2025)
This study investigated the relationship between top management leadership skills and faculty research capability as drivers of institutional internationalization efforts among State Universities and Colleges (SUCs) in Region XI. The research examined the leadership skills of SUC administrators, assessed faculty research capabilities, explored the extent of institutional internationalization initiatives, and determined how management leadership supports these efforts. Employing a phenomenological approach within Creswell’s qualitative research framework, the study utilized in-depth interviews (IDIs) and focus group discussions (FGDs) with 17 academic professionals to capture their lived experiences. Participants shared perspectives on leadership practices among SUC administrators, faculty research development, and internationalization initiatives within their institutions. Findings revealed that top management leadership skills and faculty research capability significantly impact institutional internationalization efforts among SUCs in Region XI. The study contributes to understanding how academic leadership and research capacity development serve as catalysts for enhancing the international profile of regional higher education institutions.